Teacher’s strategy in Instilling Integrated Religious Character in The Learning of Elementary Schools - Eka Susanti; Suyatno Suyatno (Universitas Ahmad Dahlan, 2021)
This study describes the teacher’s strategy to instill integrated religious character in Muhammadiyah elementary school Demangan of Yogyakarta. This qualitative study research with a study case. The research data was collected through observation, interviews, and documentation. In this study, The research subject consisted of the principal, fifth-grade teacher, the students, and student guardians. The data validity test used the triangulation technique and sources. Data analysis techniques included data reduction, data presentation, and conclusion. The research result showed that the teacher’s strategy is to instill integrated religious character in learning by integrating religious character in the entire learning components, religious character internalization, religious character habituation, and religious character role model.